Analysis of Liquefaction Potential in The Youtefa Bay Area, Jayapura City - Emilyano Joel O. Wayangkau; Duha Awaluddin Kurniatullah; Dewi Ana Rusim; Alfian Adie Chandra; Helen Gianditha Wayangkau (Jurnal Indonesia Sosial Teknologi, 2024)
The distribution of soil in Jayapura City, especially the Youtefa Bay area, consists of three dominant soil types that then form the stratigraphy of the local soil layer, namely allifial deposits, silt silt/silt clay, and fine, uniformly grained sand. Soil conditions like this have great potential for liquefaction, especially since this area is mostly passed by fault lines that have the potential to cause earthquakes. The groundwater table factor that is very close to the surface soil is also an important factor in the occurrence of liquifaction. There are 2 ways to analyze the potential for liquifaction, namely by laboratory test and from field test data. The approach to calculating field test data is CPT (Cone Penetration Test) testing. The results obtained were the Cyclic Stress Ratio (CSR) value and the Cyclic Resistance Ratio (CRR) value obtained by simulating seismic data using an earthquake strength of 6.5 on the riter scale and a pic ground acceleration value (0.3), then based on the results of the cone penetration test (CPT)/Sondir showed a maximum value of CRR 2.88, a minimum value of 0.21, a maximum CSR value of 3.70, a minimum value of 2.25. The maximum value of FS is 0.97, the minimum value is 0.07. There are 6 points at the research location that have the potential for liquefaction (Very High), namely points S1, S2, S5, S7, S8, S10, while 3 points with medium potential (High), namely points S3, S4, S9 for those with low potential (Low) S6.